Agricultural intensification and damages to human health in relation to agrochemicals: Application of artificial intelligence. (April 2019) - Elahi, Ehsan; Weijun, Cui; Zhang, Huiming; Nazeer, Majid
Highlights: Pesticides and pure N were overused by 45.2% and 37.2%, respectively. Pesticide exposure caused dizziness, nausea, diarrhoea, skin, and eye irritation. Farmers had little knowledge of recommended and safe use of pesticides. Majority of farmers not used protective measures during pesticide application. Limited or no use of protective measures caused unacceptable human health damages. Abstract: The indiscriminate use of agrochemicals for the maximization of the crop yield has adverse effects on the air, water, soil, non-target organisms, and human health. Reducing the impacts of agrochemicals on the environment and human health is instrumental for agricultural sustainability and cleaner production. To date, limited studies have focused on the issues of rice intensification, realistic agrochemical-saving targets, human health concerns associated with agrochemical use, and protective measures that may help to reduce occupational exposure during pesticide application. Cross-sectional data of 360 rice growers were collected from September to October 2017 from 9 districts of Punjab, Pakistan using multistage sampling technique. A combination of descriptive statistics and econometric methods was used in this study. The results found a 60% rice efficiency, which is evidence that farm resources were not utilized at the optimal level. An artificial neural network method (ANN) was suggested to reduce the quantity of pesticides and pure N by 45.2 and 37.2%, respectively, at a given level of rice yield. However, pure P, pure K, zinc, and farm yard manure (FYM) were recommended to increase by 490.9, 18.4, 64.7, and 32.6%, respectively than existing level. The results of the Cobb-Douglas (CD) production function found positive significant impacts of pure P, pure K, zinc, and FYM on the rice yield. According to a Tobit regression model, the rice efficiency significantly increased with education and farming experience, while it decreased with increasing crop area under rice cultivation and the distance among rice plots. Pesticide application caused skin irritation, eye irritation, cough, dizziness, nausea, and diarrhoea in 33, 41.7, 38, 30.5, 27.5, and 12% of the population, respectively. A few cases of death (3%) and serious illness (10%) due to drinking pesticides intentionally or unintentionally were also discovered. A Poisson regression model confirmed that pesticide poisoning significantly increased the incidence of eye irritation, skin irritation, dizziness, cough, and nausea during pesticide application. Moreover, cases of occupational health exposure were significantly higher among those who did not adopt protective measures. A negative binomial regression suggested that the use of protective measures, such as protective clothes, goggles, mask, gloves and boots, during chemical application significantly reduced the risk to human health. A lack of education and awareness about the appropriate and safe use of agrochemicals are the main reasons for the overutilization of pesticides and for the negative consequences on human health. This study stresses the importance of using agrochemicals at the recommended level and instead using bio-chemicals for agricultural sustainability and to protect human health. Moreover, the use of pesticide protective measures is highly recommended to avoid respiratory and dermal exposure to pesticides.